Analysis of analog and RF behaviors in junctionless double gate vertical MOSFET - K. E. Kaharudin; Z. A. F. M. Napiah; F. Salehuddin; A. S. M. Zain; Ameer F. Roslan (Institute of Advanced Engineering and Science, 2020)
The prime obstacle in continuing the transistor’s scaling is to maintain ultra-shallow source/drain (S/D) junctions with high doping concentration gradient, which definitely demands an advanced and complicated S/D and channel engineering. Junctionless transistor configuration has been found to be an alternative device structure in which the junction and doping gradients could be totally eliminated, thus simplifying the fabrication process. In this paper, a process simulation has been performed to study the impact of junctionless configuration on the analog and RF behaviors of double-gate vertical MOSFET. The result proves that the performance of n-channel junctionless double-gate vertical MOSFET (n-JLDGVM) is slightly better than the junction double-gate vertical MOSFET (n-JDGVM). Junctionless device exhibits better analog behaviors as the transconductance (gm) is increased by approximately 4%. In term of RF behaviors, the junctionless device exhibits 3.4% and 7% higher cut-off frequency (fT) and gain band-width product (GBW) respectively over the junction device.